High expression of insulin receptor on tumour‐associated blood vessels in invasive bladder cancer predicts poor overall and progression‐free survival. Issue 2 (3rd May 2017) - Roudnicky, Filip; Dieterich, Lothar C; Poyet, Cedric; Buser, Lorenz; Wild, Peter; Tang, Dave; Camenzind, Peter; Ho, Chien Hsien; Otto, Vivianne I; Detmar, Michael
Abstract: Bladder cancer is a frequently recurring disease with a very poor prognosis once progressed to invasive stages, and tumour‐associated blood vessels play a crucial role in this process. In order to identify novel biomarkers associated with progression, we isolated blood vascular endothelial cells (BECs) from human invasive bladder cancers and matched normal bladder tissue, and found that tumour‐associated BECs greatly up‐regulated the expression of insulin receptor (INSR). High expression of INSR on BECs of invasive bladder cancers was significantly associated with shorter progression‐free and overall survival. Furthermore, increased expression of the INSR ligand IGF‐2 in invasive bladder cancers was associated with reduced overall survival. INSR may therefore represent a novel biomarker to predict cancer progression. Mechanistically, we observed pronounced hypoxia in human bladder cancer tissue, and found a positive correlation between the expression of the hypoxia marker gene GLUT1 and vascular INSR expression, indicating that hypoxia drives INSR expression in tumour‐associated blood vessels. In line with this, exposure of cultured BECs and human bladder cancer cell lines to hypoxia led to increased expression of INSR and IGF‐2, respectively, and IGF‐2 increased BEC migration through the activation of INSR in vitro . Taken together, we identified vascular INSR expression as a potential biomarker for progression in bladder cancer. Furthermore, our data suggest that IGF‐2/INSR mediated paracrine crosstalk between bladder cancer cells and endothelial cells is functionally involved in tumour angiogenesis and may thus represent a new therapeutic target. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.